Analysis of Effective Sentences at the Syntactic Level in the News Entitled “Serapan APBD Sumbar Rendah, Abaikan Pusat?” - Zebua, Agnes Fitriani; Aneskhi, Fitra; Rasyid, Yulianti (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
The purpose of this study was to describe the effectiveness of the sentence in the Singgalang news entitled "Serapan APBD Sumbar Rendah, Abaikan Pusat". The effectiveness of this sentence concerns syntax errors, which are often found in news writing. The most obvious error is at the syntax level. Based on this, this study uses a qualitative method with a descriptive approach. To obtain the data, the observation technique was chosen as the data collection method. This is done by observing the use of language and note-taking techniques to record the analyzed structures. Furthermore, the data were analyzed using the distribution method. The results of the research regarding the analysis of language errors in the syntactic field contained in the article include sentence effectiveness. This finding further strengthens the paradigm that news text writing often ignores the principles of Indonesian syntax.